Clinical characteristics of hemophilia A patients with hemarthrosis - Setyo Handryastuti; Djajadiman Gatot; Arwin A. P. Akib (Indonesian Pediatric Society, 2002)
Background Hemarthrosis is the most frequent bleeding manifestation of severe hemophilia. Repeated hemarthrosis will cause chronic arthropathy, which results in a physical disability.Objectives To obtain data of clinical characteristics of hemophilia- A patients with hemarthrosis (particularly chronic hemarthrosis) and to know the effect of on-demand therapy on joints of the patients.Methods We evaluated 102 hemophilia A patients in Pediatric Hematology and Oncology Division, Cipto Mangunkusumo Hospital for 6 months beginning from March 2001.Results The number of cases of chronic hemarthrosis was 22%,smaller than previous study (54%). Chronic hemarthrosis mostly occurred in hemophilia A patients who aged between 13-18 years, had severe hemophilia A and frequency of hemarthrosis more than 12 times a year, and also patients who did not receive adequate therapy. The joint which most frequently suffered from hemarthrosis were knee (26%), ankle (23%) and elbow (21%). The critical period for the first hemarthrosis was at the age of 2-12 years, and repeatedÂ hemarthrosis episodes commonly occurred at the age 6-18 yearsowing to the child's increasing physical activities.Conclusion Hemarthrosis can be prevented and anticipated. It is important to notice the critical period when first hemarthrosisand repeated hemarthrosis occur. The certain joints like knee, ankle and elbow must be given more attention due to the risk ofrepeated hemarthrosis.